Warunki meteorologiczne na Szrenicy w latach 2018-2020 - Mendel, Karolina; Szyga-Pluta, Katarzyna (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
The article presents the weather conditions on Mount Szrenica, located in the Karkonosze range in the Sudetes, in 2018–2020. The data come from the Database of Integrated Monitoring of Natural Environment. An average temperature in the presented time was 4,0oC, an average yearly precipitation was 1245.8 mm, an average atmospheric pressure 865.3 hPa, average wind speed 5.1 m/s, average snow cover height 66.3 cm, the sun shone for 1881 hours in a year. Changes in individual values compared to the results published earlier prove the impact of global changes also in this area.